Dissecting a Zombie: Joint Analysis of Density and Resistivity Models Reveals Shallow Structure and Possible Sulfide Deposition at Uturuncu Volcano, Bolivia - MacQueen, Patricia; Gottsmann, Joachim; Pritchard, Matthew E.; Young , Nicola; Ticona J, Faustino; Ticona, Eusebio (Tico); Tintaya, Ruben (Frontiers in Earth Science, 2021)
The recent identification of unrest at multiple volcanoes that have not erupted in over 10 kyr presents an intriguing scientific problem. How can we distinguish between unrest signaling impending eruption after kyr of repose and non-magmatic unrest at a waning volcanic system? After ca. 250 kyr without a known eruption, in recent decades Uturuncu volcano in Bolivia has exhibited multiple signs of unrest, making the classification of this system as “active”, “dormant”, or “extinct” a complex question. Previous work identified anomalous low resistivity zones at <10 km depth with ambiguous interpretations. We investigate subsurface structure at Uturuncu with new gravity data and analysis, and compare these data with existing geophysical data sets. We collected new gravity data on the edifice in November 2018 with 1.5 km spacing, ±15 μGal precision, and ±5 cm positioning precision, improving the resolution of existing gravity data at Uturuncu. This high quality data set permitted both gradient analysis and full 3-D geophysical inversion, revealing a 5 km diameter, positive density anomaly beneath the summit of Uturuncu (1.5–3.5 km depth) and a 20 km diameter arc-shaped negative density anomaly around the volcano (0.5–7.5 depth). These structures often align with resistivity anomalies previously detected beneath Uturuncu, although the relationship is complex, with the two models highlighting different components of a common structure. Based on a joint analysis of the density and resistivity models, we interpret the positive density anomaly as a zone of sulfide deposition with connected brines, and the negative density arc as a surrounding zone of hydrothermal alteration. Based on this analysis we suggest that the unrest at Uturuncu is unlikely to be pre-eruptive. This study shows the value of joint analysis of multiple types of geophysical data in evaluating volcanic subsurface structure at a waning volcanic center.